“Padėk, Dieve!” (Tradiciniai gero linkėjimai dirbančiam žmogui) - Jasiūnaitė, Birutė (Kalbotyra, 1997)
The present article is an attempt to analyse constructions relating to the etiquette of the Lithuanian. The analysis is based on widely cited examples of greetings used by the members of the peasant community in various situations, working in the fields or at home (we mean haymaking time, harvest time, flax-pulling season, baking, weaving). About 20 situations reflecting different means of politeness were distinguished. The most universal formula “God help you!” became the title of this article.